OTU-10 Impact of cirrhosis severity on clinical outcomes in hepatocellular carcinoma in england. (June 2019) - Driver, Robert; Burton, Anya; Downing, Amy; Marshall, Aileen; Morris, Eva; Rowe, Ian
Abstract : Background: Survival in hepatocellular carcinoma (HCC) is determined by both cancer stage and severity of underlying liver disease. International guidelines based on data from clinical trials provide a benchmark for survival following different HCC treatments [1]. The aim of this study was to estimate the impact of cirrhosis severity on overall survival for patients with HCC and cirrhosis in England. Methods: All patients registered with a new diagnosis of HCC between 2007 and 2016 in England were identified from the National Cancer Registration and Analysis Service records, which are linked to the Hospital Episode Statistics dataset. These records were used to identify patients with cirrhosis, their baseline characteristics and HCC treatments received. Cirrhosis severity at HCC diagnosis was categorised by the Baveno IV consensus: compensated cirrhosis defined by stage 1 (no ascites or varices) and stage 2 (non-bleeding varices), and decompensated cirrhosis defined by stage 3 (ascites) or stage 4 (bleeding varices). Following HCC treatment, the linked record was analysed to identify subsequent decompensation events during 5 years of follow-up. Competing risk models were used to describe the risk of death after decompensation ('death due to liver failure') and the risk of death without decompensation ('death due to HCC'). Results: Among 19, 436 patients registered with HCC, 11, 337 were identified with cirrhosis and were included in the analyses. The majority of patients (6, 207, 54.7%) were ineligible for specific HCC treatment and received best supportive care. The most common HCC treatments were ablation (1, 228 patients, 10.8%) and trans-arterial chemoembolization (TACE; 2, 021 patients, 17.8%). Among those who received ablation, the median survival was 41.9 months in those without varices at HCC diagnosis, 33.8 months in those with non-bleeding varices, and 23.9 months in those with previous decompensation (P<0.001). Among those who received TACE, median overall survival in the same groups was 20.7, 17.9, and 14.0 months respectively (P <0.001). Competing risk analyses showed that this excess mortality was associated with an increased risk of death due to liver failure for both treatment modalities. These estimates compare with international benchmarks of median survival of 36 months in patients treated with ablation and 20 months for those treated with TACE. Conclusions: Overall survival in patients with HCC and cirrhosis in England are in line with international benchmarks. Survival is negatively associated with increasing cirrhosis severity for the most common treatment modalities. Considering the impact of previous decompensation on outcomes is critical in treatment selection for HCC. Reference: EASL-EORTC clinical practice guidelines: management of hepatocellular carcinoma. J Hepatol . 2012;56(4).